2021
DOI: 10.1111/pala.12518
|View full text |Cite
|
Sign up to set email alerts
|

Comparing surface digitization techniques in palaeontology using visual perceptual metrics and distance computations between 3D meshes

Abstract: The use of surface digitization techniques and methods in palaeontology has increased in the last two decades, mainly due to recent improvements in devices and software. However, many digitization efforts are published only as 3D models, with only a few details on the exact protocols used and sometimes not even indicating how to access these digital data, thus reducing the long‐term reusability of the obtained files. It is important to include this information, as the applied techniques and workflows have sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Past analyses showed that surface scans, photogrammetry, and CT scans produced 3D reconstructions with similar quality (Falkingham, 2012; Fau et al, 2016), which is especially true for large specimens at the resolution reached here. Furthermore, Soodmand et al (2018) showed that there was no significant difference between 3D models of a femur digitized with both CT and surface scanner; and Dìez Dìaz et al (2021) showed that, despite the superior visual quality of photogrammetry, the difference in the geometry of 3D meshes generated from photogrammetry and an Artec EVA scanner was even lower than reported in Fau et al (2016) (e.g., <0.01 mm against 0.6 mm). Finally, Waltenberger et al (2021) showed that osteological 3D models obtained from surface scans, photogrammetry, and CT scans could be combined in a single analysis when using 3D GMM.…”
Section: Methodsmentioning
confidence: 99%
“…Past analyses showed that surface scans, photogrammetry, and CT scans produced 3D reconstructions with similar quality (Falkingham, 2012; Fau et al, 2016), which is especially true for large specimens at the resolution reached here. Furthermore, Soodmand et al (2018) showed that there was no significant difference between 3D models of a femur digitized with both CT and surface scanner; and Dìez Dìaz et al (2021) showed that, despite the superior visual quality of photogrammetry, the difference in the geometry of 3D meshes generated from photogrammetry and an Artec EVA scanner was even lower than reported in Fau et al (2016) (e.g., <0.01 mm against 0.6 mm). Finally, Waltenberger et al (2021) showed that osteological 3D models obtained from surface scans, photogrammetry, and CT scans could be combined in a single analysis when using 3D GMM.…”
Section: Methodsmentioning
confidence: 99%
“…Iterative polygonal modelling is not limited to cross-sectional information, this method can be used in conjunction with muscle surface scan data that can (1) streamline processes in which the user can also collect dissection data at the same time as muscular configurations, and (2) further minimise costs and time commitment for the user because expensive CT-scan data after lengthy staining processes do not need to be collected 1 . However, it is not required to use surface scan-technology that can be expensive and prohibitive itself 85 , 87 ; photogrammetry is an alternative possibility 84 , 86 , in which the user can further minimise total costs by even using a personal smartphone rather than an expensive camera or laser scanning 87 to capture a series of photographs and then subsequently use freeware to build 3D models of each muscle layer (e.g. 1 , 83 ).…”
Section: Methodsmentioning
confidence: 99%
“…Digitization (alternatively referred to as "digitalization"; Moya-Costa et al, 2019) initiates 3D digital restoration by converting a fossil into digital form using either penetrative slice-based scanning methods (Cunningham et al, 2014;Sutton et al, 2014;Lautenschlager, 2016a;Lautenschlager, 2016b;Lautenschlager, 2017;Sutton et al, 2017) or light-based surface scanning methods (Díez Díaz et al, 2021). These processes yield digital 3D files of various formats, which are influenced by settings or parameters during scanning.…”
Section: Terminology and Stages Of Digital Restorationmentioning
confidence: 99%